Monitoring of the productivity and quality of the winter rye grain of the new yield in the Bryansk region throughout 2012–2016 - F. I. Klimenkov; S. M. Gradskov; О. A. Shchuklina; N. L. Kuznetsova; I. N. Klimenkova; O. I. Ermolenko (Зерновое хозяйство России)
Implementing the provisions of the State Program for the Development of Agriculture and the regulation of agricultural products, raw materials and food markets, the Ministry of Agriculture of the Russian Federation annually monitors the gross collection and evaluation of commodity and consumer quality of grain harvested in the current year. In the current paper there has been carried out an estimation of the gross yield and productivity of winter rye; there has been characterized a ratio of the volumes of the produced food grain and non-food (feed) grain. There has been given an information on grain according to their classes and quality indicators, which allows quickly generating batches of grain balances, in order to make a balanced decision on the volume of grain export or import, on introducing grain into the state intervention fund, on a rational use of grain resources, both inside Bryansk region, and the country as a whole. It is possible to build a reliable grain balance on the basis of the monitoring results of the grain quality of the new yield in the scope of studies of composite samples taken from at least 50% of the gross yield.